Lumacaftor/ivacaftor therapy fails to increase insulin secretion in F508del/F508del CF patients - Moheet, Amir (J Cyst Fibros, 2020)
BACKGROUND: Glucose tolerance abnormalities including cystic fibrosis related diabetes (CFRD) are common in patients with cystic fibrosis (CF). The underlying pathophysiology is not fully understood. Emerging evidence suggests that CFTR dysfunction may directly or indirectly impact β-cell function, offering the potential for improvement with CFTR modulator therapy. In small pilot studies, treatment with ivacaftor improved insulin secretion in patients with the G551D CFTR mutation. In the current study, we examined the impact of lumacaftor/ivacaftor therapy on glucose tolerance and insulin secretion in patients with CF who were homozygous for the F508del mutation. METHODS: 39 subjects from the PROSPECT Part B study who had been prescribed lumacaftor/ivacaftor by their CF care team at a CF Foundation’s Therapeutic Development Network center were recruited. Subjects underwent 2-hour oral glucose tolerance tests (OGTTs) at baseline prior to first dose of lumacaftor/ivacaftor, and at 3, 6 and 12 months on therapy. OGTT glucose, insulin and c-peptide parameters were compared. RESULTS: Compared to baseline, OGTT fasting and 2 hour glucose levels, glucose area under the curve, insulin area under the curve and time to peak insulin level were not significantly different at 3, 6 and 12 months on lumacaftor/ivacaftor therapy. Similarly, C-peptide levels were no different. CONCLUSIONS: Lumacaftor/ivacaftor therapy did not improve insulin secretion or glucose tolerance in patients with CF who were homozygous for the F508del mutation.